New confinement index and new perspective for comparing countries - COVID-19. (October 2021) - da Costa, Joaquim Pinto; Garcia, André
Highlights: We propose a new way of comparison between countries that avoids the main difficulties in the comparison by using threedimensional trajectories for this type of data. We also introduce a new index to analyze the level of confinement that each country was subject to overtime, based on the community mobility reports published by Google and Principal Component Analysis. We include a review section on clustering analysis for longitudinal data. This type of data is very popular and common in biomedicine applications. Finally, by using longitudinal clustering, we divide the European countries into similar groups according to the COVID-19 infections and also to the confinement index. Abstract: Background and objective: In the difficult problem of comparing countries regarding their lockdown measures or deaths caused by the COVID-19, there is still no agreement on what is the best strategy to follow. Thus, we propose a new way of comparison countries that avoids the main difficulties in the comparison by using three-dimensional trajectories for this type of data. Methods: We introduce a new index to analyze the level of confinement that each country was subject to overtime, based on the Community Mobility Reports published by Google resorting to Principal Component Analysis. Subsequently, by using longitudinal clustering, we divide the European countries into similar groups according to the COVID-19 obits and also to the confinement index. However, to make the most out of the clustering methods we resort to artificial longitudinal data to evaluate both the methods and the indices. Results: By using artificial data, we discover that Calinski–Harabasz outperformed other internal indices in indicating the real number of clusters. The tests also suggested that K -means with Euclidean distance was the best method among the ones studied. With the application to both the mobility and fatalities datasets, we found two groups in each one. Conclusions: Our analysis enables us to discover that European northern countries had more mobility during the first confinement and that the deaths caused by COVID-19 started to drop around the 40th day since the first death.